A tin–bismuth alloy electrode for the cathodic stripping voltammetric determination of iron in coastal waters. Issue 12 (21st June 2015) - Lin, Mingyue; Pan, Dawei; Hu, Xueping; Li, Fei; Han, Haitao
<x xml:space="preserve">Abstract</x> We employed a home-made tin–bismuth alloy electrode (SnBiE) as the working electrode with 1-(2-piridylazo)-2-naphthol (PAN) as the complexing ligand to detect trace iron.